Metal nanoparticles: a theranostic nanotool against cancer. Issue 9 (September 2015) - Sharma, Harshita; Mishra, Pawan K.; Talegaonkar, Sushama; Vaidya, Bhuvaneshwar
Highlights Metal nanoparticles have been extensively explored for the management of various disease conditions including cancer. Metal nanoparticles showed inherent anticancer activity and can also be used as drug carriers. Metal nanoparticles have also been explored as diagnostic and imaging agents. Toxicity issues of metal nanoparticles should be considered before clinical application.